2015
DOI: 10.1002/jat.3125
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of silicon dioxide, silver and iron oxide nanoparticles after repeated oral administration to rats

Abstract: Although silicon dioxide (SiO2), silver (Ag) and iron oxide (Fe2O3) nanoparticles are widely used in diverse applications from food to biomedicine, in vivo toxicities of these nanoparticles exposed via the oral route remain highly controversial. To examine the systemic toxicity of these nanoparticles, well-dispersed nanoparticles were orally administered to Sprague-Dawley rats daily over a 13-week period. Based on the results of an acute toxicity and a 14-day repeated toxicity study, 975.9, 1030.5 and 1000 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 55 publications
3
65
1
1
Order By: Relevance
“…49 A study where iron oxide nanoparticles were orally administered at about 3 mg/kg body weight to rats over a 13-week period reported that they did not accumulate in tissues or produce toxicity. 54 Another rat feeding study with much higher oral dose (250-1000 mg/kg body weight) of iron oxide nanoparticles for 13-week also did not find their tissue accumulation or toxicity in both male or female rats. 50 Titanium dioxide (TiO 2 ) nanoparticles.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 95%
“…49 A study where iron oxide nanoparticles were orally administered at about 3 mg/kg body weight to rats over a 13-week period reported that they did not accumulate in tissues or produce toxicity. 54 Another rat feeding study with much higher oral dose (250-1000 mg/kg body weight) of iron oxide nanoparticles for 13-week also did not find their tissue accumulation or toxicity in both male or female rats. 50 Titanium dioxide (TiO 2 ) nanoparticles.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 95%
“…A subchronic toxicity of red iron oxide nanoparticles (60–118 nm) was investigated by Yun et al. () in a 13‐week oral toxicity study according to the OECD TG 408 (OECD, ). Rats received daily doses of 250, 500 or 1,000 mg/kg bw per day for 13 weeks by gavage.…”
Section: Assessmentmentioning
confidence: 99%
“…A subchronic toxicity of red iron oxide nanoparticles (60–118 nm) was investigated by Yun et al. () in a 13‐week oral toxicity study according to the OECD TG 408 (OECD, ). Rats received daily doses of 250, 500 or 1 000 mg/kg bw/day for 13 weeks by gavage.…”
Section: Assessmentmentioning
confidence: 99%